PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN DI SD(IMPLEMENTASI DAN TANTANGANNYA DIKELAS) - Lusiana (CV. ADIBA AISHA AMIRA, 2026)
This study discusses the implementation of the scientific approach in elementary school learning and the challenges faced in classroom practice. The scientific approach, which consists of observing, questioning, experimenting, associating, and communicating, is expected to improve students’ critical thinking skills and active participation. This research uses a qualitative descriptive method through classroom observation and literature review. The results show that the scientific approach can create more interactive and meaningful learning processes. However, teachers still face several challenges such as limited time allocation, differences in students’ abilities, and lack of learning facilities. Therefore, teachers need creativity and good classroom management skills to implement this approach effectively